Effect of different patient peak arrivals on an emergency department via discrete event simulation: a case study. (March 2022) - Fava, Giordano; Giovannelli, Tommaso; Messedaglia, Mauro; Roma, Massimo
Emergency department (ED) overcrowding is a well-recognized worldwide phenomenon which affects the quality of emergency care. A direct consequence of overcrowding is a long wait for visit and treatment of people who require primary care, possibly endangering the lives of critical patients. Healthcare management literature devoted to analyze ED operational policies is very wide, and many approaches have been proposed to address this important problem. However, less attention has been given to patient peak arrivals caused by the occurrence of some critical events which can strongly strain the operational efficiency of an ED. In this paper, we consider the particular case study of a medium-size ED located in a region of Central Italy recently hit by a severe earthquake, aiming at assessing the effects of such an occurrence on the ED operation. In particular, we propose a discrete event simulation (DES) model to analyze the patient flows through this ED, simulating unusual operational conditions due to a critical event, like a natural disaster, which causes a sudden spike in the number of patient arrivals. The availability of detailed data concerning the ED processes enabled building an accurate DES model and performing extensive scenario analyses. The model provides a valid decision support system for the ED managers in assessing specific emergency plans to be activated in case of mass casualty disasters.